(untitled) (Research, Society and Development, 2021)
The aim of this study was to characterize the essential oil (EO) of red aroeira seeds and to evaluate their antimicrobial and antioxidant activities. The EO was extracted by hydrodistillation in a Clevenger-type device with a yield of 9.83% ± 0.31%; it was characterized by Fourier-transform infrared spectroscopy (FTIR), gas chromatography and mass spectrometry (GC-MS) to determine its physical-chemical characteristics. The EO showed acidity of 0.2814 mg KOH g-1, a 1.4763 ± 0.0014 refraction index and density of 0.9365 ± 0.01656 g cm-3. Through the FTIR, the absorption bands of the EO indicated the presence of the following components: limonene, delta -3-carene, a pinene and myrcene. By GC-MS the major compounds found were 4(10)-thujene (44.97%) α-Pinene (20.42%), o-Cymene (12.76%) and p-Menth-1-en-4-ol, (R)-(-)-(6.74%). Antimicrobial activity was evaluated against Gram-positive and Gram-negative bacteria. In the microdilution method, no inhibiting activity was found in the tested concentrations (serial dilutions from 25.6 to 0.05 μL mL-1) and in the disk diffusion method, inhibition halos were observed only when pure EO was added. Antioxidant activity was evaluated by DPPH (oxidation-reduction reaction) and FRAP (iron ion reduction). In the DPPH, the obtained result was 0.01119 ± 0.0001 μmol g-1 and in FRAP, 13.813 ± 0.02187 μmol g-1, which demonstrates antioxidant activity in the two evaluated methods, indicating the possible application of the essential oil of red aroeira seeds as a natural antioxidant agent.